Effect of traditional Chinese medicine components on multidrug resistance in tumors mediated by P-glycoprotein - Xia, Xi (Oncol Lett, 2017)
Multidrug resistance (MDR) is a major cause of chemotherapy failure. It occurs when an organism is resistant to one type of drug, but also develops resistance to other drugs with different structures and targets. There is a high incidence of MDR in cancer chemotherapy, therefore, finding an effective and non-toxic MDR reversal agent is an important goal, particularly for P-glycoprotein-mediated MDR in cancer. Improvements continue to be made to the status and understanding of traditional Chinese medicine (TCM), due to the advantages of low toxicity and relatively minor side effects. Therefore TCM is currently being used in the treatment of various types of diseases. In recent years, numerous components of TCM have been identified to be effective in reversing MDR by downregulating expression of the drug transporter membrane protein, recovering changes in enzymes involved in detoxification and metabolism and repairing the cell apoptosis pathway. The present study summarizes the anticancerous properties and MDR reversing components of traditional medicinal plants commonly used in the treatment of cancer.